Development and Validation of the Needs Assessment Scale for Innovative Technology Approaches to Dental Screening - Deepika Yadav; D. Sunil Kumar; M.S Mallikarjunaswamy; Vanishri Arun; G. Hari Prakash; S Sunita (Journal of Indian Association of Public Health Dentistry)
Background: The prevalence of dental disorders is high worldwide, including in India, with disparities in access to care. Novel dental devices, such as digital radiography, dental lasers, and electrical impedance spectroscopy, could improve diagnosis and treatment, but demand among health-care practitioners needs assessment. Aim: This study aimed to develop a comprehensive tool for assessing community dental screening needs using novel technologies. Methodology: A preliminary questionnaire was developed based on expert consultation, validated through face validation, and revised based on subject experts’ suggestions. Statistical analysis was performed using the SPSS software version 25, and validity and reliability were checked using Cronbach’s alpha coefficient. The tool was validated for effectiveness and feasibility among health-care professionals, and a final version was drafted. Results: A tool for assessing dental caries screening needs was validated by experts and pilot-tested with health-care professionals and interns. The tool was found to have good internal consistency with Cronbach’s alpha values >0.7 in each domain, except for the expressed needs domain. The overall Cronbach’s alpha for all domains was 0.812. The tool categorized the participants’ overall dental screening needs, with 91.7% showing a moderate need for dental screening with novel technologies. Conclusion: The dental needs assessment tool has good internal consistency and validation but needs refinement for improved generalizability. It shows the potential to enhance dental care.